2018
DOI: 10.5897/jvmah2018.0677
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Mycobacterium bovis in Jalisco, Mexico: Tracing back sources of infection

Abstract: Bovine tuberculosis (bTB) is a disease of cattle that presents risk to public health, causing severe economic losses to the livestock industry and difficulty in eradication because of its complex epidemiology. The aim of this study was to identify relationships between Mycobacterium bovis strains from cattle in the State of Jalisco, and those of other States of México. Molecular fingerprints of 337 M. bovis isolates from Jalisco, and 1152 from other States of México were included in the study. Isolates were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The most frequent spoligotypes were SB0673 (32%) and SB0121 (26%), which coincides with reports made by Gutierrez-Reyes et al (7) and Milian-Suazo et al (13). On the other hand, contrary to what some studies reported, which was that SB0140 was the most frequent (5,21), we did not find this spoligotype in the region of Altos Sur. In one study that also analysed M. bovis isolates from Jalisco (5), out of 14 spoligotypes found only four coincided with those found in our research (SB0673, SB0121, SB0145, SB0971); these are the most common and frequently reported for Mexico (13).…”
Section: Discussionsupporting
confidence: 85%
“…The most frequent spoligotypes were SB0673 (32%) and SB0121 (26%), which coincides with reports made by Gutierrez-Reyes et al (7) and Milian-Suazo et al (13). On the other hand, contrary to what some studies reported, which was that SB0140 was the most frequent (5,21), we did not find this spoligotype in the region of Altos Sur. In one study that also analysed M. bovis isolates from Jalisco (5), out of 14 spoligotypes found only four coincided with those found in our research (SB0673, SB0121, SB0145, SB0971); these are the most common and frequently reported for Mexico (13).…”
Section: Discussionsupporting
confidence: 85%